2020
DOI: 10.3390/jcm9072291
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-Infant Bonding in Women with Postpartum Psychosis and Severe Postpartum Depression: A Clinical Cohort Study

Abstract: Mother-to-infant bonding is important for long-term child development. The aim of this study was to investigate bonding in women admitted to a Mother and Baby Unit with postpartum depression (PD, n = 64) and postpartum psychosis (PP, n = 91). Participants completed the Postpartum Bonding Questionnaire (PBQ), the Edinburgh Postnatal Depression Scale (EPDS) and the Young Mania Rating Scale (YMRS) weekly during admission. At admission, 57.1% of women with PD had impaired bonding, compared to only 17.6% of women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
2
30
0
2
Order By: Relevance
“…Delavari et al 10 found that maternal–fetal attachment is one of the factors contributing to postpartum depression. Mother‐to‐baby attachment is thought to form the foundation for the child's later attachment 11 . The negative mother–infant relationship that occurs in the first years of the baby's life has long‐term negative consequences in emotional, social, and cognitive terms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delavari et al 10 found that maternal–fetal attachment is one of the factors contributing to postpartum depression. Mother‐to‐baby attachment is thought to form the foundation for the child's later attachment 11 . The negative mother–infant relationship that occurs in the first years of the baby's life has long‐term negative consequences in emotional, social, and cognitive terms.…”
Section: Introductionmentioning
confidence: 99%
“…Mother-to-baby attachment is thought to form the foundation for the child's later attachment. 11 The negative mother-infant relationship that occurs in the first years of the baby's life has longterm negative consequences in emotional, social, and cognitive terms. Therefore, the development of mother-baby bond is important.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, PPD—experienced by about 13% of women with a recent live birth in the United States in 2018 32 —is an intense persistent sadness that can interfere with a woman's ability to care for herself and the baby, 33 last for up to 3 years in some women, 34 and elevate depressive symptoms up to 11 years after childbirth. 35 Worryingly, the rate of women with a depression diagnosis at delivery increased sevenfold between 2000 and 2015.…”
Section: Thirty Years Of Scientific Advances Results In Better Health...mentioning
confidence: 99%
“…With reducing associated factors within the birthing environment critical for optimising clinical outcomes (International Consortium for Health Outcome Measurement, 2016). In addition, there is compelling evidence that links maternal well-being to that of the infant (Bang et al, 2020;Gilden et al, 2020;Sliwerski, Kossakowska, Jarecka, Switalska, & Bielawska-Batorowicz, 2020). Thus, appreciating women's birth experiences is crucial towards improving relationships with staff, the clinical environment, care provided, experiences of interventions, and understandings of their associations with outcomes (Alfaro Blazquez, Corchon, & Ferrer Ferrandiz, 2017;Nijagal et al, 2018;Nilver, Begley, & Berg, 2017).…”
Section: Introductionmentioning
confidence: 99%